The effect of problem posing learning combined concept map on critical thinking skill, motivation, and student outcomes on environmental pollution subject at MAS Babun Najah Banda Aceh - Wirdatul Wahida; Hasanuddin Hasanuddin; Djufri Djufri (Jurnal Edubio Tropika, 2018)
The objective of this study was to determine the implementation of Problem Posing Learning Model combined with Mind Mapping to improve students’ critical thinking skills, learning motivation, for environmental pollution material. The data collected in March 2017. The method employed in this study was the Randomized Pretest-Posttest Control/Group Design method. This research conducted on four classes X MIA 1 was chosen as the experiment class I, X MIA 2 as experiment class II, and X MIA 3 as experiment class III. Meanwhile, class X MIA 4 used as a control class. The research instruments used were a series of tests to assess students, critical thinking skills to measure students. The gained data were analyzed using variance analysis (ANOVA) at a significant level of 0.05. The results of variance analysis showed that Fcount Ftable showing thinking skill 290.05 2.70. Based on these findings, it can be concluded that the implementation of Problem Posing learning model combined with mind map influenced students’ critical thinking skills for environmental pollution material at MAS Babun Najah Banda Aceh.Keywords: Problem Posing, Concept Map, Critical Thinking, Learning Motivation and Learning Outcomes.